Survey of imazethapyr-resistant common ragweed (Ambrosia artemisiifolia L.) in Quebec - Marsan-Pelletier, Félix; Vanasse, Anne; Simard, Marie-Josée; Cuerrier, Marie-Edith (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2019)
Common ragweed (Ambrosia artemisiifolia L.) is widespread in soybean (Glycine max L.) fields in southern Québec. Biotypes resistant to ALS (group 2) herbicides are commonly reported in conventional crops where these herbicides are used. Reported cases are voluntary and potentially underestimate the occurrence of resistance. A survey was therefore undertaken in 2014 and 2015 in soybean fields treated with a Group 2 herbicide. Common ragweed seeds were collected from 123 fields. Seedlings were grown and tested for resistance using the recommended rate of imazethapyr (100.8 g a.e. ha-1). Weed populations were classified as susceptible, developing resistance (less than one third of plants classified as resistant) or resistant (at least one third of plants were resistant). Twenty populations were then selected based on these resistance levels and treated with four doses of the herbicide (0, 100.8, 201.6, and 403.2 g a.e. ha-1). Resistance to imazethapyr was detected in 81% of samples (21.1% were classified as developing resistance and 59.4% were classified as resistant). Populations classified as developing resistance had a resistance factor of 1.04, while populations classified as resistant had a resistance factor greater than 5. These results confirm the presence of multiple populations of imazethapyr-resistant common ragweed in Quebec.